A seed‐like proteome in oil‐rich tubers. (16th September 2022) - Niemeyer, Philipp William; Irisarri, Iker; Scholz, Patricia; Schmitt, Kerstin; Valerius, Oliver; Braus, Gerhard H.; Herrfurth, Cornelia; Feussner, Ivo; Sharma, Shrikant; Carlsson, Anders S.; de Vries, Jan; Hofvander, Per; et al.
SUMMARY: There are numerous examples of plant organs or developmental stages that are desiccation‐tolerant and can withstand extended periods of severe water loss. One prime example are seeds and pollen of many spermatophytes. However, in some plants, also vegetative organs can be desiccation‐tolerant. One example are the tubers of yellow nutsedge ( Cyperus esculentus ), which also store large amounts of lipids similar to seeds. Interestingly, the closest known relative, purple nutsedge ( Cyperus rotundus ), generates tubers that do not accumulate oil and are not desiccation‐tolerant. We generated nanoLC‐MS/MS‐based proteomes of yellow nutsedge in five replicates of four stages of tuber development and compared them to the proteomes of roots and leaves, yielding 2257 distinct protein groups. Our data reveal a striking upregulation of hallmark proteins of seeds in the tubers. A deeper comparison to the tuber proteome of the close relative purple nutsedge ( C. rotundus ) and a previously published proteome of Arabidopsis seeds and seedlings indicates that indeed a seed‐like proteome was found in yellow but not purple nutsedge. This was further supported by an analysis of the proteome of a lipid droplet‐enriched fraction of yellow nutsedge, which also displayed seed‐like characteristics. One reason for the differences between the two nutsedge species might be the expression of certain transcription factors homologous to ABSCISIC ACID INSENSITIVE3, WRINKLED1, and LEAFY COTYLEDON1 that drive gene expression in Arabidopsis seed embryos. Significance Statement: In this work we compare the protein composition of the tubers of yellow nutsedge ( Cyperus esculentus ), which are desiccation‐tolerant and oil‐rich, with the tubers of purple nutsedge ( Cyperus rotundus ), which do not have these characteristics. We discovered that yellow but not purple nutsedge has a proteome similar to that of seeds from other species.